2021
DOI: 10.3390/en14040871
|View full text |Cite
|
Sign up to set email alerts
|

Development, Calibration and Validation of an Internal Air Temperature Model for a Naturally Ventilated Nearly Zero Energy Building: Comparison of Model Types and Calibration Methods

Abstract: In this study, a grey box (GB) model for simulating internal air temperatures in a naturally ventilated nearly zero energy building (nZEB) was developed and calibrated, using multiple data configurations for model parameter selection and an automatic calibration algorithm. The GB model was compared to a white box (WB) model for the same application using identical calibration and validation datasets. Calibrating the GB model using only one week of data produced very accurate results for the calibration periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…A systematic modelling approach outlined in Figure 2, using a methodology based on existing published studies [26][27][28]33] was adopted to capture the complexity of this application. The main aim of this approach is to adequately reproduce, and subsequently predict, the internal air temperature ramps within the indoor occupied space being modelled during shut down of the AHU, based on a number of defined input variables.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic modelling approach outlined in Figure 2, using a methodology based on existing published studies [26][27][28]33] was adopted to capture the complexity of this application. The main aim of this approach is to adequately reproduce, and subsequently predict, the internal air temperature ramps within the indoor occupied space being modelled during shut down of the AHU, based on a number of defined input variables.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The model was calibrated on one day of actual measured conditions and validated across the remaining 8 days of measured values using the C1V8 process [26], thereby allowing the model to be trained effectively on empirical conditions whilst minimising bias and reducing the risk of over fitting. As the AHU was run on a consistent daily schedule with minimal operational variations, it was found that additional validation days were more valuable than calibration days to gain insights and build confidence in the accuracy of the outputs.…”
Section: Description Of the Case Study Buildingmentioning
confidence: 99%
See 3 more Smart Citations